Pengaruh Fitoremediasi Eichornia crassipes Terhadap Kadar Fosfat dan Amonia di Instalasi Pengolahan Limbah Cair RSUP Dr. Sardjito Yogyakarta - Rini Purwasari; Mohammad Mirza Fauzie; Haryono Haryono (Sanitasi: Jurnal Kesehatan Lingkungan, 2012)
As the byproduct of it’s activities, Dr Sardjito General Hospital produces wastewater which may contain hazardous microorganisms and substances. Two ofthe chemicals in the hospital’s waste water which had been exceeding the threshold were phosphate and ammonia. Excessive phosphate may lead tosepticemia, while ammonia makes irritation and disturbs chlor disinfection. One of the treat-ments which can be used is phytoremediation by using Eichornia crassipes. The aim of the research was to identify the effect of this water plant in repair-ing the quality of the waste water by conducting an experiment with pre test post test with control group design. The plants were placed at sedimentation II chamber and were acclimatized beforehand. The results show that the mean decrease of phosphate in the control group was 0,554 mg/l, while in the treat-ment group was 0,916 mg/l. For ammonia, the mean decrease in the control group was 2,732 mg/l, and in the treatment group it was 5,829 mg/l. The data were then analyzed by using Mann Whitney test at 0,05 signification level, and yielded p-values of 0,020 and 0,026 for phosphate and ammonia reduction respectively, which means that the phytoremediation was significantly effective for reducing the two chemicals. The phosphate were reduced 22,973% and the ammonia were of 28,33%.